Association between occupational NO₂ exposure and hypertension risk: a PRISMA-based systematic review with risk-of-bias assessment - Ayudhia Rachmawati; Morrin Choirunnisa Thohira; Muhammad Aidil Fitrah; Vivi Filia Elvira (International Journal of Public Health Science (IJPHS), 2026)
Nitrogen dioxide (NO₂) is a major air pollutant generated from fossil fuel combustion in transportation and industrial activities and is associated with adverse health effects. Prolonged exposure to NO₂ may induce chronic inflammation and endothelial dysfunction, which contribute to the development of hypertension. This study aimed to systematically review the association between NO₂ exposure and the incidence of hypertension among workers. The review was conducted in accordance with PRISMA guidelines, with literature searches performed in Google Scholar, PubMed, and ScienceDirect for publications from 2020 to 2025. Inclusion criteria comprised full-text articles in English or Indonesian employing observational study designs (cross-sectional, cohort, case-control, or ecological) and involving workers in both formal and informal sectors. Eligible studies examined NO₂ exposure as the independent variable and hypertension as the outcome. Of 2,051 records identified, five studies met the inclusion criteria, originating from China and Nigeria. Risk of bias was assessed using the office of health assessment and translation (OHAT) risk of bias tool. The findings demonstrated a consistent association between NO₂ exposure and an increased risk of hypertension, particularly in poorly ventilated work environments. These results underscore the importance of improving workplace air quality management, strengthening exposure monitoring, and implementing preventive occupational health strategies.